Diterpene chemical space of Aeollanthus buchnerianus Briq. aerial part - Gabin T. M. Bitchagno; Nathan Reynolds; Monique S. J. Simmonds (Natural Products and Bioprospecting)
Abstract The Plectranthinae clade, which includes genera such as Plectranthus, Ocimum, and Aeollanthus, is well known for its diverse array of diterpenoids. While numerous studies have deepened the understanding of diterpene diversity across the clade, Aeollanthus species remain underexplored, with only two studies focusing on their diterpene profiles. The NMR-based chemical profiling of the EtOAc leaf extract of the rocky and succulent species Aeollanthus buchnerianus Briq. reveals a range of diterpenes with isopimarane and abietane skeletons including several previously unreported analogues. Interestingly, the isolated compounds provided insights into the breakdown patterns of both diterpene classes by examining the product ions in their MS2 spectra. These data offer valuable information for evaluating the taxonomic position of this species in relation to other species within the clade. Graphical Abstract